DESAIN APLIKASI AKUNTANSI BERBASIS MICROSOFT EXCELL DI MAGIC LAUNDRY SOLO - Magdalena Nany; Raniati Bokol; Mujiyono (Institut Agama Kristen Negeri Kupang, 2026)
Financial management plays a crucial role for MSMEs, enabling them to conduct thorough financial planning, control budget usage, maximize the utilization of available resources, and improve overall value and performance. Various available applications significantly assist MSMEs in recording financial reports, one of which is Microsoft Excel. The financial application was designed for Magic Laundry Solo. Data collection techniques used included observation, literature review, needs identification, and initial design. Regular evaluation and documentation of the financial application are also required to ensure it can be truly implemented and meets the needs of laundry owners. A Microsoft Excel-based laundry financial application is a practical, economical, and easy-to-implement solution for home-based laundry business owners and MSMEs. Business owners can now implement simple accounting in a practical and easy manner, which is very useful in monitoring financial conditions, evaluating business performance, and supporting financial decision-making